Evaluation of Parties and Coalitions After Parliamentary Elections - Andranik Tangian (Fondazione Eni Enrico Mattei (FEEM), 2006)
Five leading German political parties and their coalitions are evaluated with regard to party manifestos and results of the 2005 parliamentary elections. For this purpose, the party manifestos are converted into Yes/No answers to 95 topical questions (Relax the protection against dismissals? Close nuclear power plants? etc.). On each question, every party represents its adherents as well as those of the parties with the same position. Therefore, a party usually represents a larger group than its voters. The popularity of a party is understood to be the percentage of the electorate represented, averaged on all the 95 questions. The universality of a party is the frequency of representing a majority of electors. The questions are considered either unweighted, or weighted by an expert, or weighted by the number of GOOGLE-results for given keywords (the more important the question, the more documents in the Internet). The weighting however plays a negligible role because the party answers are backed up by the party ``ideology'' which determines a high intra-question correlation. The SPD (Social-Democratic Party) did not receive the highest percentage of votes, remains nevertheless the most popular and the most universal German party. A comparison of the election results with the position of German Trade Union Federation (DGB) reveals its high representativeness as well. Finally, all coalitions with two and three parties are also evaluated. The coalition CDU/SPD (which is currently in power) is the most popular, and the coalition SPD/Green/Left-Party (which failed due to personal conflicts) is the most universal.
Keywords: D71; 330; Parliamentary Election; Fractions; Coalitions; Theory of Voting; Mathematical Theory of Democracy; Indices of Popularity and Universality; German Trade Union Federation (DGB)